2010
DOI: 10.4049/jimmunol.0900062
|View full text |Cite
|
Sign up to set email alerts
|

CD155 Is Involved in Negative Selection and Is Required To Retain Terminally Maturing CD8 T Cells in Thymus

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 57 publications
2
20
2
Order By: Relevance
“…Additionally, CD155 is a ligand for the Ig-like receptors DNAM-1 (CD226), Tactile (CD96), and T cell immunoreceptor with Ig and ITIM domains (TIGIT) on T cells and NK cells (18)(19)(20)(21)(22). Mice deficient in CD155 show diminished humoral immune responses and thymic retention of mature CD8 + cells (16,(23)(24)(25). Although several studies have demonstrated various functions of CD155, particularly on nonhematopoietic cells, the role of CD155 in lymphocyte function remains undefined.…”
mentioning
confidence: 99%
“…Additionally, CD155 is a ligand for the Ig-like receptors DNAM-1 (CD226), Tactile (CD96), and T cell immunoreceptor with Ig and ITIM domains (TIGIT) on T cells and NK cells (18)(19)(20)(21)(22). Mice deficient in CD155 show diminished humoral immune responses and thymic retention of mature CD8 + cells (16,(23)(24)(25). Although several studies have demonstrated various functions of CD155, particularly on nonhematopoietic cells, the role of CD155 in lymphocyte function remains undefined.…”
mentioning
confidence: 99%
“…12 CD155 knockout mice are characterized by reduced accumulation of CD8 single-positive thymocytes and by defective humoral immune responses in response to oral vaccination. 13,14 With regard to ECs, antibody-mediated neutralization of CD155 prevents monocyte and T-cell receptor-dependent effector memory T-cell transendothelial migration in vitro. 15,16 Most of the immunologic effects of CD155 are mediated by its interaction with DNAX accessory molecule-1 (DNAM-1) (also called CD226) or CD96 on the surface of leukocytes.…”
mentioning
confidence: 99%
“…In addition to ECs, it is interesting to note that we did not observe CD155 expression on resting human CD8 T cells, although CD155 expression has been documented on resting CD8 T cells in mice. 13 Systemic elimination of CD155 in mice results in a reduction in the number of mature CD8 SP thymocytes and defects in antibody class-switching in response to oral administration of antigen 13,14,28 . Furthermore, DNAM-1 expression on mouse CD8 T cells is needed for optimal CD8 T-cell proliferation and development of cytotoxic effector function in response to activation by B cells that overexpress CD155.…”
mentioning
confidence: 99%
“…In thymus medulla, the single positive T-cells that show affinity to self-antigens presented on MHC molecules receive pro-apoptotic signal (Le Borgne et al 2009, Qiu et al 2010, Atibalentja et al 2009, McCaughtry et al 2008. This elimination of auto-reactive T-cells is called negative selection, and its main purpose is to prevent the development of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%